Games and Bereavement How Video Games Represent Attachment, Loss and Grief - Harrer, Sabine (Edition Medienwissenschaft, 2018)
How can videogames portray love and loss? »Games and Bereavement« answers this question by analysing five videogames and conducting a participatory design study with grievers. Sabine Harrer offers both theoretical and practical perspectives on videogames and grief and suggests a design model for videogames to include grievers into game development. Overall, she explores how videogames can be used as contemporary medium for personal storytelling.